Socio-political priorities for the preservation of historical and cultural heritage in Kazakhstan - Aryn, Е.М.; Kishkenbayeva, Ж.К. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Currently, in strategically important state documents of the Republic of Kazakhstan, alongside a profound recognition of cultural heritage as a value, new demands are emerging for the comprehensive celebration of history and culture and for the scientific justification of its potential as a resource for peace, stability, and socio-economic development. These new demands highlight the need for comprehensive research on the re-evaluation of the genesis of values and their significance in intercultural and interspatial dialogue among communities and nations for domestic social and humanities sciences. This article aims to analyze the foundations of socio-political priorities in preserving historical and cultural heritage in the country at the intersection of interdisciplinary sciences. The relevance of the article lies in its examination of the key directions for the socio-political institutionalization of the Kazakh people’s historical and cultural heritage, analyzing the factors and conditions for integrating the spiritual potential of historical and cultural values into the state-political development of contemporary Kazakhstan. The article enables the assessment of the level and effectiveness of the institutional foundations for preserving historical and cultural heritage, including their differentiation in regional and sectoral contexts. The practical significance of the conclusions and recommendations presented in the article is to establish priorities for transitioning to a new model of socio-cultural policy in the new Kazakhstan.